AWARENESS OF NAFLD AMONG RESIDENTS OF АLMATY CITY SUFFERING FROM DIABETES TYPE 2 DIABETES - B.P. Sultanova; E.A. Slavko; G.K. Mukazhanova; A.N. Nurbakyt (Interdisciplinary Approaches to Medicine, 2023)
Acute lymphoblastic leukemia (ALL) is the most common childhood malignancy with variety of nonspecific symptoms that may present with signs and symptoms related to extramedullary involvement, therefore, leads to delayed diagnosis of ALL in children. Aim: This study aims to determine the prevalence of extramedullary manifestations at the initial presentation of acute lymphoblastic leukemia in children. Method: This is a retrospective, cross-sectional study assessing medical records of 73 patient newly diagnosed (ALL) at Almaty Scientific center of pediatrics and surgery during-2020. The children had a mean age of 6.9 ±4.27 years. The female and male patients made 46 (63 %) and 27(37 %) respectively. children with acute lymphoblastic disease were classified into two subtypes (B-cell ALL and T-cell ALL) according to the WHO classification. Data earned from the study were enrolled within a directory also statistical analysis was done by applying the software (SPSS) version 26.0. Categorical variables resembled using the chi-square test or Fisher's exact test, as appropriate.Result: In this study, the most common extramedullary initial signs and symptoms of ALL were related to hepatic system 49 (67.1 %) and gastrointestinal symptom 43 (58.9%).The additional extramedullary presentations of ALL in order of frequency include; lymphadenopathy  20 (27.4%) , musculoskeletal system 19 (26%) urinary system 9 (12.3 %), Respiratory 9 (12.3 %) , Neurological system 5 (6.8%) orbital presentation 3 (4.1%), neurologic signs 8 (9%%), pericardial involvement 1 (1.4%), and the other miscellaneous presentations 3 (4.1%).Conclusion: This study showed that a significant number of ALL patients present with variety of extramedullary symptoms that pediatrician must become familiar with those to detect some atypical cases of leukemia early on. And increase the probable chance of survival by early detection.